PERLINDUNGAN HUKUM KORBAN PELECEHAN SEKSUAL TERHADAP ANAK (Studi Putusan Pengadilan Negeri Sidoarjo Nomor: 597/Pid.Sus/2023/PN Sda.) - Ekasari, Agustina; Astutik, Sri; Prawesthi, Wahyu (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2024)
The consideration of the person giving the decision, namely the judge, in handing down a decision regarding an act that tends towards child abuse which leads to a criminal offense is based on several elements to determine the final decision that will be taken. The judge considered that this case had several bases, namely the element of each person, the element of committing violence or threats of violence forcing the child to have sexual intercourse with him or another person, all of which had been explained in detail. Then regarding the judge's decision regarding the juvenile criminal justice system, there are no obstacles, where this choice is equivalent to the principles that speak about the Juvenile Law Enforcement Framework. One of the places in his choice, the judge chose to be imprisoned for a long time with a probationary period of half a year in prison, deducted from the period of imprisonment and a monetary fine of Rp. 2,000,000,- (two million rupiah) with the provision that if the fine cannot be paid, it will be replaced by detention for more than 90 days. In fact, article 71 paragraph (3) states that assuming the punishment is in the form of a financial fine, the total punishment will be imposed as detention and the fine will be replaced with work preparation. This implies that fines for children who are struggling with the law should be fixed on the assumption that they cannot meet the agreed fines, for example, work preparation. Keywords: Legal perspective, sexual harassment, minors